Simulasi Perdagangan Kontrak Berjangka CPO pada Bursa Malaysia dengan Cyclic Forecasting Periode Januari-Desember 2009 - Tomy G. Soemapradja; Billy Utama Suria (Bina Nusantara University, 2011)
Crude palm oil (CPO) is one commodity that could be consumed and also as one alternative of non- fossil fuel: biodiesel. Since 2006, CPO commodity trade has its significant raise, followed by forward contract trade. The increasing of CPO price in 2006 is the lowest in historic analysis data period 2007-2008. Cyclic forecasting model is used following cycle pattern of twice-a-year, with a combination of Solver function in Ms. Excel that could minimize MSE as 161,02, Beta 0,0688 and intercept in -11,0396. Cyclic forecasting period is supposed to be used along with technical analysis, using stop loss to reduce risk. It needs additional research to adjust confidence level so VaR value is not too high that could fix trading strategy along this research.